Chronicles and the Priestly Literature of the Hebrew Bible - Jeon, Jaeyoung; Jonker, Louis C. (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2021)
This volume aims to examine the literary and socio-historical relationship between the Books of Chronicles and the priestly literature in the Pentateuch and in Ezekiel. Experts across this body of literature come together to examine the connections and interactions between specific texts, ideas, and socio-historical contexts of the literary works, as well as explore broader themes in the relationship between them.